Mutagenicity, antimutagenicity and cytotoxicity evaluation of South African Podocarpus species - Abdillahi,H.S.; Luc Verschaeve; Finnie,J.F.; Van Staden,J. (J.Ethnopharmacol., 2012)
ETHNOPHARMACOLOGICAL RELEVANCE: Four species of Podocarpus are used in traditional medicine both in human and animal healthcare in South Africa. In vitro pharmacological screening of leaf and stem extracts of these species exhibited potent antimicrobial, anti-inflammatory, anti-tyrosinase, anthelmintic, acetylcholinesterase inhibitory and antioxidant activities. AIM OF THE STUDY: To investigate the mutagenicity, antimutagenicity and cytotoxicity effects of leaf and stem extract of South African Podocarpus species. MATERIAL AND METHODS: The mutagenicity and cytotoxic effects of extracts from four species of Podocarpus were tested using the Salmonella/microsome assay with and without metabolic activation, based on the plate-incorporation method and neutral red uptake (NRU) assay respectively. Five Salmonella typhimurium tester strains; TA98, TA100, TA102, TA1535 and TA1537 were used for mutagenicity testing. The relative cytotoxicity of the extracts was assessed by determining their NI(50) values (50% inhibition of NRU). RESULTS: The extracts did not show any mutagenic effects against all the tester strains with or without metabolic activation. All extracts demonstrated a strong antimutagenic effect on the mutations induced by 4NQO, decreasing its mutagenic effect in a dose-dependent manner. Strong cytotoxic effects were exhibited by petroleum ether extracts as compared to 80% ethanol extracts. When HepG2 cells were in contact with plant extracts in an increasing concentration, slopes of NRU decreased (highest-lowest %) following a concentration-dependent pattern. For 80% ethanol extracts, the most toxic extract in terms of percentage viability was leaves of Podocarpus falcatus whereby at 0.2 mg/ml, the viability of the cells was 38.9%. Stem extract of Podocarpus latifolius was the most toxic among PE extracts, giving a percentage viability of 46.4 at 0.1 mg/ml. CONCLUSION: Absence of mutagenicity does not indicate lack of toxicity, as was observed from these extracts. These findings will help in assessing the safety measures to be considered in the use of these species and also the need to determine the cytotoxic potential of these species against various forms of human cancer cells
Keywords: Antimutagenicity; cytotoxicity; mutagenicity; Podocarpus